Mental Health in Persons With Chronic Myeloid Leukemia During the SARS-CoV-2 Pandemic: The Need for Increased Access to Health Care Services - Mei Bao; Sen Yang; Robert Peter Gale; Yanli Zhang; Xiaoli Liu; Huanling Zhu; Rong Liang; Bingcheng Liu; Li Zhou; Zongru Li; Xuelin Dou; Dayu Shi; et al. (Frontiers in Psychiatry, 2021)
Mental health problems in the general population have been reported during the SARS-CoV-2 pandemic; however, there were rare data in persons with chronic myeloid leukemia (CML). Therefore, we performed a cross-sectional study on mental health evaluated using the 9-item Patient Health Questionnaire (PHQ-9; depression), the 7-item Generalized Anxiety Disorder (GAD-7; anxiety), and the 22-item Impact of Event Scale—Revised (IES-R; distress), including subscales of avoidance, intrusion, and hyper-arousal in persons with CML, non-cancer persons, and immediate family members of persons with cancer as controls (≥16 years) by an online survey. Data from 3,197 persons with CML and 7,256 controls were collected. In multivariate analyses, CML was significantly associated with moderate to severe depression (OR = 1.6; 95% Confidence Interval [CI], 1.4, 1.9; p < 0.001), anxiety (OR = 1.4 [1.1, 1.7]; p = 0.001), distress (OR = 1.3 [1.1, 1.5]; p < 0.001), and hyper-arousal (OR = 1.5 [1.3, 1.6]; p < 0.001). Moreover, delay in regular monitoring was significantly associated with depression (OR 1.3 [1.0, 1.7]; p = 0.024), anxiety (OR = 1.3 [1.0, 1.8]; p = 0.044), avoidance (OR = 1.2 [1.0, 1.4]; p = 0.017), and intrusion (OR = 1.2 [1.0, 1.4]; p = 0.057); tyrosine kinase-inhibitor dose reduction or discontinuation, depression (OR = 1.9 [1.3, 2.8]; p = 0.001), distress (OR = 2.0 [1.4, 2.8]; p < 0.001), avoidance (OR = 1.6 [1.2, 2.1]; p = 0.004), intrusion (OR = 1.6 [1.1, 2.1]; p = 0.006), and hyper-arousal (OR = 1.3 [1.0, 1.8]; p = 0.088). We concluded that persons with CML during the SARS-CoV-2 pandemic have worse mental health including depression, anxiety, and distress symptoms. Decreasing or stopping monitoring or dose resulted in adverse mental health consequences.